THE LAW OF BORROWED GOODS (ARIYAH) ACCORDING TO SCHOLARS ACROSS SCHOOLS OF THOUGHT - Susandi, Aidil (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This research aims to examine the Islamic legal perspective on ariyah (loan of goods) across different schools of thought. The urgency of this study lies in the need to understand the legal foundations of social cooperation, particularly regarding the often-practiced yet underexplored issue of lending items among individuals. The research employs a qualitative, descriptive-analytical method, analyzing primary hadith sources and scholarly opinions from various Islamic legal schools concerning the rules, types, pillars, and liabilities of ariyah. The findings indicate that ariyah is a permissible social contract in Islam, but its legal implications vary across schools, especially concerning the return of borrowed items and responsibility for potential damage